A Few Psychometric Properties of Horizontal and Vertical Individualism and Collectivism Scale in Two Countries: A Pilot Study in Lithuania and Turkey - Vadvilavičius, Tadas; Stelmokienė, Aurelija (Psichologija, 2025)
Culture is an important contextual factor affecting human attitudes and behavior. Reliable and valid instruments are needed to measure this complex phenomenon. The psychometric properties of the Horizontal and Vertical Individualism and Collectivism Scale (Triandis & Gelfand, 1998) were tested in two countries – Lithuania (n = 110) and Turkey (n = 80). Internal reliability and factorial validity were investigated. The results revealed adequate internal reliability for group analysis and confirmed the factorial structure for a four-factor model. Limitations and recommendations for future research are discussed.